An Examination of the Mental Health Experiences of Peacekeeping Operation (PKO) Officers: A Case Study of the Ghana Armed Forces - Tsakpo, G. K. (University of Ghana, 2025)
Globally, peacekeeping operations (PKOs) has contributed towards the stability of conflict prone states and nations. Ghana as a member of the United Nations has played crucial roles towards promoting peacekeeping and peace enforcement initiatives. However, peacekeeping officers encounter several challenges and prominent amongst them are mental health issues which affects predominantly the quality of health of the military. The study sought to underscore the importance of providing mental health services to peacekeeping officers by examining the mental health experiences of peacekeeping officers from the Ghana Armed Forces. The study was guided by the transactional model of stress and coping theory and bio-psychosocial theory. The research study employed a qualitative methodological approach utilizing a personal in-depth interview technique. Using a purposive sample of twenty-five (25) selected peacekeeping officers from the Ghana Armed Forces, the study findings revealed a moderate knowledge of peacekeeping officers on the issue of mental health. The study found out that at the pre-deployment phase, orientations are organized for selected officers taking part in the PKOs. The orientations do cover all issues relating to specific rules and expectation, rules of engagement, cultural awareness, responsivity to protect, conflict dynamics, coordination of operations and effective community engagements. In addition, the study found out that some of the conditions or situations that give rise to stress include volatile situations, prolonged exposure to combat warfare, excessive workload and isolation. In terms of the mental health issues experienced by some of the peacekeepers, stress, anxiety, fear, chronic depression and trauma, substance abuse, sleep disruptions and suicidal tendencies were amongst the list. The findings further reveal that some of the coping strategies or mechanisms adopted by peacekeeping officers in order to navigate complexity of mental health include confiding in their peers, relaxation, sleeping, taking short breaks, spiritual coping or faith-based affirmations, therapeutic mechanisms, reduction of workload and engaging in physical exercises. Moreover, the study found out that some mental health services available to peacekeeping officers were largely centred on referral to the health team and counselling services. The study findings further reveal deep sited barriers that peacekeeping officers encounter in their efforts to receive treatment which include discrimination, loss of one’s job, labelled as mentally unfit and stigmatization. The study recommends awareness campaigns of mental health support systems at the pre-deployment stage, routine psychological surveillance, welfare, enhancing health services, organizing campaigns against stigma and evaluation of mental health following a mission. By implementing these recommendations, the Ghana Armed Forces would be better placed to cater for the mental health of its peacekeeping officers whilst ensuring that they fulfill their mission of peacekeeping successfully.
MA. International Affairs and Diplomacy
Keywords: peacekeeping operations (PKOs); conflict; Ghana